THE ROLE AND SIGNIFICANCE OF FINE ARTS IN PRESCHOOL EDUCATION - Nomonova Azizakhan Nozimzhan Qizi (Western European Studies, 2024)
This article describes the role of fine arts in preschool educational organizations and visual activities in the development of children's creativity.
Keywords: visual activity; applique; plasticine; gouache